Związki zawodowe a rynek pracy w Unii Europejskiej - JAGUSIAK, Bogusław (Przegląd Politologiczny, 2018)
The aim of this study is to present the opportunities for trade unions to influence the labor market in the EU. The economic crisis in the EU has affected its labor markets to varying degrees. In the analysis of selected examples it can be clearly seen that the countries that have survived the crisis in the labor market better are those where the labor market is flexible, i.e. where, although people can easily lose one job, they are relatively likely to find another. EU states undertake to make labor relations more flexible, to further diversify employment forms, or to move salary negotiations to lower levels, thus eliminating state intervention in labor markets. Local EU labor markets have become a part of a supranational system of free flow of workers. European integration has generated common problems in the labor market, where trade unions need to undertake joint efforts to increase the flexibility, mobility and efficiency of the labor force, to improve labor market programs and provide for more efficient collaboration of social partners. This also follows from the protective function trade unions are supposed to play in the unified European market, and from an attempt to solve the issue of whether the expansion of trade union activity to the European level is effective in looking for compromise on the labor market.